Integrative teaching and learning: reflections of a complex world in the curricula of primary teacher education programs - Peltomaa, Iida-Maria; Hietamäki, Ulla; Toikka, Teppo; Mård, Nina; Tigert, Johanna M.; Harmoinen, Sari; Kaasinen, Arja; Kärkkäinen, Sirpa; Tarnanen, Mirja; Maunula, Minna; Kimanen, Anuleena; Kujala, Tiina; et al. (Routledge, Taylor & Francis Group, 2026)
Background: Acting in a changing world demands a holistic understanding of complex phenomena. Teacher education must therefore equip candidates with both knowledge and skills in integrative teaching and learning.
Purpose: This study investigates how integrative teaching and learning are reflected in the curricula of Finnish primary teacher education programs during the academic year 2024–2025.
Methods: The curricula of ten Finnish primary teacher education programs were analyzed using both data-driven and theory-guided content analysis.
Results: Five categories of courses reflect integrative teaching and learning: explicitly designed courses, subject-specific courses, integrative courses, studies in educational theory, and supervised teaching practice. These revealed four main approaches to integration: general integration, curriculum-driven integration, subject-based integration, and transdisciplinary integration.
Conclusions: The findings provide tools for reflection and curriculum development in primary teacher education.